2017
DOI: 10.1016/j.mod.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest and cancer: Divergent travelers on similar paths

Abstract: Neural crest cells are multipotent progenitors that dynamically interpret diverse microenvironments to migrate significant distances as a loosely associated collective and contribute to many tissues in the developing vertebrate embryo. Uncovering details of neural crest migration has helped to inform a general understanding of collective cell migration, including that which occurs during cancer metastasis. Here, we discuss several commonalities and differences of neural crest and cancer cell migration and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 167 publications
0
51
0
Order By: Relevance
“…The neural crest is a unique population of highly migratory stem cells that contributes to the development and formation of multiple tissues in vertebrates (Bronner & LeDouarin, ; Gallik et al, ). Migrating neural crest cells (NCCs) progress through the cell cycle with variable timing, rates, and frequency, the details of which are likely critical for the initiation of migration and maintenance of migratory stream dynamics (Burstyn‐Cohen & Kalcheim, ; Ridenour et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The neural crest is a unique population of highly migratory stem cells that contributes to the development and formation of multiple tissues in vertebrates (Bronner & LeDouarin, ; Gallik et al, ). Migrating neural crest cells (NCCs) progress through the cell cycle with variable timing, rates, and frequency, the details of which are likely critical for the initiation of migration and maintenance of migratory stream dynamics (Burstyn‐Cohen & Kalcheim, ; Ridenour et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While well-studied in cancer ( Masciullo et al, 2003 ; Sarhadi et al, 2006 ), little was known about its developmental function in neural crest cells. Given the parallels between the mechanisms that regulate delamination, migration, proliferation, and survival of neural crest cells and tumor cells ( Gallik et al, 2017 ), we sought to characterize the expression of Hmga1 during neural crest development.…”
Section: Resultsmentioning
confidence: 99%
“…42 Neural-crestderived and cancer cells are reported to have similar molecular and cell biological regulatory systems. 43 This suggests that osteoblasts cultured from bone harvested from the mandible may offer a more suitable cell population for the study of VEGFR inhibitor targets. 44 This research has used primary HAOBs and found that VEGFR1 was the predominant VEGF receptor present during the osteogenic mineralization process in vitro.…”
Section: Discussionmentioning
confidence: 99%